Effects of Spirulina platensis and Chlorella vulgaris on the immune system and reproduction of fish - Joshua, Wizilla Janti; Zulperi, Zarirah (Universiti Putra Malaysia Press, 2020)
This review briefly highlights previous studies on the effects of Spirulina platensis and Chlorella vulgaris on the health and reproduction of fish. These microalgae have diverse potentials. This study can be used as a stepping stone in advancing the aquafeed industry by formulating microalgae-based feeds. It can be made to specifically enhanced the health status of fish and its reproductive system through the supplementation and/or replacement of fishmeal or other plant proteins such as soybean meal. Hence, it could be more sustainable than depending on natural fish stocks. The usage of antibiotics and vaccines to solve the issue of disease outbreak in aquaculture, as well as the usage of hormones for the growth and reproduction of fish, can also be replaced by the usage of S. platensis and C. vulgaris. The inclusion of these microalgae in fish feed has affected hemathological parameters and survival in fish as it boosts the numbers of white and red blood cells and thus affecting the immunity-stimulating capacity in fish. Besides, these microalgae also affect the fecundity and survival of fish eggs and thus directly affecting the reproduction performance of fish. Spirulina platensis affects eggs production and survival in fish whereas C. vulgaris enhances oxidative stress that affects the reproduction of White rabbits. This review aimed to deliver the results on the research of S. platensis and C. vulgaris on the immunity and reproduction of various fish species.